Non-surgical approach for repairing perforations of pars tensa in tympanic membrane using TCA cauterization - Gaur, Sushil; Patel, Monika; Hirdesh, Prince; Singh, Vandana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Tympanic membrane perforations occurring due to mucosal COM usually require surgical interventions for repair (myringoplasty or tympanoplasty) depending on the size and site of the perforation and the ossicular chain continuity. Various studies have shown TCA cautery as an efficacious non surgical method for repairing small and medium sized TM perforations. This technique was successfully used and popularized for repairing small and medium sized perforations by Derlacki in 1953. Methods: In this study we included dry pars tensa perforations in 100 patients occurring due to trauma or unresolved cases after inflammation/infection of middle ear. 50% w/v trichloro acetic acid was used for a maximum number of 5 applications at the margins of the perforations which were followed up for the next one year. Results: In this study, involving a total of 125 perforations (75 unilateral and 50 bilateral), success rate was high among the patients with traumatic perforations and small sized perforations while a few number of perforations only reduced in size, which were later corrected with surgical approaches (myringoplasty/tympanoplasty). The overall success rate achieved in this study was 72.16%. Conclusions: Though there are various materials and methods available for this procedure, the principle remains the same. This technique should be attempted for patients that fit the criteria for undergoing this procedure before being undertaken for surgical approaches to minimize the risks and cost burden associated with surgery and anesthesia.